A pilot RCT of a school nurse delivered intervention to reduce student anxiety. Issue 2 (4th March 2021) - Ginsburg, Golda S.; Drake, Kelly L.; Muggeo, Michela A.; Stewart, Catherine E.; Pikulski, Paige J.; Zheng, Di; Harel, Ofer
Abstract : The goal of this study was to evaluate the feasibility and impact of brief school-nurse-administered interventions for reducing anxiety. Thirty school nurses in Connecticut and Maryland were randomly assigned to deliver the Child Anxiety Learning Modules (CALM; n = 14) or CALM–Relaxation only (CALM-R; n = 16). Students ( N = 54) were ages 5–12 ( M age = 8; 84.9% White; 68.5% female) with elevated anxiety symptoms and/or anxiety disorders. Feasibility was assessed based on recruitment, retention, attendance, training and intervention satisfaction, and intervention adherence. Multiple informants, including independent evaluators (IEs), completed measures of clinical improvement at postintervention and at a 3-month follow-up. Of nurses in CALM and CALM-R, 62% and 81%, respectively, enrolled a student and completed an average of 6 sessions. Youth retention was 85% and 94% in CALM and CALM-R, respectively. Training and intervention satisfaction were high. At postintervention and follow-up, youth in both groups showed significant reductions in anxiety and related symptoms and improvements in functioning. Within-group effect sizes were medium to large, and between-group effect sizes were small. Task shifting responsibility for delivering brief mental health interventions to school nurses is feasible and shows promise for reducing anxiety and related impairment. This approach may also be integrated within a response to intervention model used in schools. Public Health Significance : Brief school-nurse-administered anxiety reduction interventions were shown to be feasible and had a positive impact on student anxiety and related impairment highlighting that school nurses can be an important school resource.